2017
DOI: 10.3892/ijo.2017.4010
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SOX4 promotes cell migration and invasion of renal cell carcinoma by inducing epithelial-mesenchymal transition

Abstract: Incomplete understanding remains in the molecular mechanisms underlying progression and metastasis of renal cancer. The transcription factor SOX4 is upregulated in various human malignancies, including renal cancer, indicating it may be involved in renal tumorigenesis. In this study, we explored this hypothesis by loss-of-function and gain-of-function assays of SOX4 in renal cancer cell lines and renal epithelial cell line. We found that specific knockdown of SOX4 in renal cancer cell lines significantly suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 45 publications
3
24
1
Order By: Relevance
“…The cellular experiments illustrated that miR-142-3p overexpression significantly repressed cell metastasis and reversed the EMT. EMT events have been widely found in the metastasis process of various cancers Ruan et al [45][46][47]. ZEB1 is a critical regulator of the EMT Zhang et al [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular experiments illustrated that miR-142-3p overexpression significantly repressed cell metastasis and reversed the EMT. EMT events have been widely found in the metastasis process of various cancers Ruan et al [45][46][47]. ZEB1 is a critical regulator of the EMT Zhang et al [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that UCA1 promoted proliferation and invasion of RCC by sponging the miR-129-3p targeting SOX4 [103]. Consistently, miR129-3p weakened migration and invasion of RCC cells [104], while SOX4 facilitated migration of RCC cells [105]. In addition, UCA1 promoted proliferation of RCC through sponging miR-495, whose downstream target is EZH2 [106].…”
Section: Renal Cell Carcinomamentioning
confidence: 91%
“…So far, several studies have been conducted to explore the roles of some SOX members including SOX4 and SOX9 in ccRCC 28,29 . Wu et al 30 and Tong et al 31 found that miR‐204 and miR‐338‐3p could inhibit cell proliferation, migration and invasion in ccRCC cell lines by directly targeting SOX4, respectively.…”
Section: Introductionmentioning
confidence: 99%